Participation and Alienation in Online Networked Learning: Social Affordances to find People and to build Social Capital - Kreijns, Karel; Van Acker, Frederik; Vermeulen, Marjan; Buuren, Hans van (Proceedings of the International Conference on Networked Learning, 2012)
The success of informal learning in large online learning networks largely depends on the existence of a sound social space that encompasses the networks of interpersonal relationships each individual has formed within this space. These personal social networks form the social capital of the individual and it is through this social capital that social interaction becomes possible and, thus, learning and knowledge co-creation can occur. It would appear that the existence of social capital is self-evident in large online learning networks as these networks are meant to connect people. However, online learning networks depend on technological systems that are incapable of transferring all the awareness cues necessary for finding people and feeling a sense of social presence. In this sense technological systems may hinder the development of a social space and the growth of social capital. Therefore, it is of utmost importance that the technological systems incorporate social affordances - subsystems or widgets that compensate for the missing awareness information and that provide mechanisms to get into contact with others and to share information. In this position paper we propose that these social affordances should orient towards promoting impromptu encounters, social navigation, and social browsing. Social affordances that enable people to experience a psychological proximity (in contrast with physical proximity) with each other will facilitate impromptu or chance encounters which will in turn lead to in increased probability of meeting people. Social affordances not only are important to get in contact with people but also because of the informal conversations that arise from these meetings. Through these conversations, a person meets new people and maintains old contacts as well as gets information that may contribute to learning. Social navigation is the process in which people use other people (direct social navigation) or other people’s traces (indirect social navigation) to find other people, perhaps the ones who possess expert knowledge and from who they may learn a lot. Social browsing is using directories of people (the social ’yellow pages’) for browsing through the user profiles stored in these directories to find other people that have similar interests or other commonalities that are important. Ultimately, social affordances enable individuals to participate in online networked learning and experience the social presence of all other members of the network who may become part of the individuals’ personal social capital. Without these affordances, individuals may feel alienated in these large online learning networks.